2015
DOI: 10.1021/acs.jpca.5b02129
|View full text |Cite
|
Sign up to set email alerts
|

Subfemtosecond Quantum Nuclear Dynamics in Water Isotopomers

Abstract: Subfemtosecond quantum dynamics studies of all water isotopomers in the X̃ (2)B1 and à (2)A1 electronic states of the cation formed by Franck-Condon ionization of the neutral ground electronic state are reported. Using the ratio of the autocorrelation functions for the isotopomers as obtained from the solution of the time-dependent Schrödinger equation in a grid representation, high-order harmonic generation signals are calculated as a function of time. The results are found to be in agreement with the availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 44 publications
(118 reference statements)
4
14
0
Order By: Relevance
“…This finding can be explained by the difference in masses between deuterium and proton, which results in different bond stretching frequencies when they are allowed to move on the same repulsive potential. Previous investigations on the photodissociation of HOD on its first excited-state PES gave similar results. It is important to mention that classical trajectory calculations on HOD 2+ gave the value of branching ratio 8.6, which is quite different from quantum results.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…This finding can be explained by the difference in masses between deuterium and proton, which results in different bond stretching frequencies when they are allowed to move on the same repulsive potential. Previous investigations on the photodissociation of HOD on its first excited-state PES gave similar results. It is important to mention that classical trajectory calculations on HOD 2+ gave the value of branching ratio 8.6, which is quite different from quantum results.…”
Section: Resultssupporting
confidence: 66%
“…Influence of other initial conditions, like initial rotational and vibrational states of HOD molecule, on dissociation dynamics of HOD 2+ is yet to understand. Previous studies showed that weak-field unimolecular photodissociation dynamics of HOD strongly depends on the initial vibrational state of HOD molecule. In this article, we would like to answer the question: Does the dissociation dynamics of HOD 2+ depend on the initial vibrational state of HOD molecule as in the case of HOD photodissociation?…”
Section: Introductionmentioning
confidence: 99%
“…[90] and need not be repeated here. Equivalently, these matrix elements can also be obtained with MCTDH time propagation [91][92][93][94][95]97]. The phase factors containing n in Eqs.…”
Section: Theorymentioning
confidence: 99%
“…[87], which however treats the vibronic dynamics in the neutral manifold. Finally, treatments of Patchkovskii and Schuurman [90], Varandas et al [91][92][93][94][95], and Arnold et al [97] fully treat cationic vibronic dynamics, but neglect neutral dynamics and their coupling to the HHG process.…”
Section: Theorymentioning
confidence: 99%
“…Molecular isomerization, [14][15][16] and in particular intramolecular hydrogen migration, 17,18 is one of the molecular processes that can be affected under asymmetric laser irradiation. Due to the light mass of the H, its migration along the molecular skeleton can be fast and completed within a few fs 19 i.e. within the pulse duration.…”
Section: Introductionmentioning
confidence: 99%